Pengaruh Bazar dan lingkungan keluarga Terhadap Minat Berwirausaha pada Mahasiswa Universitas Budi Darma - Anda Yanny (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2023)
Universitas Budi Darma always make every bazaar event the year this done For stimulate the students own entrepreneurial spirit and ready For build business Alone later after they pass. Family is the first very teach everything about life this . So is entrepreneurship . Parents job _ student This most is selling merchants _ results plant them in the market, or open business alone . And p This can said as trader . Study This aim for see how much big influence factor extrinsic and factor intrinsic student to interest entrepreneurship , namely the t test looks influence of the bazaar being held campus and environment family to interest entrepreneurship Research results This is the Bazar has influence to interest entrepreneurship for student . Temporary That Environment family No own influence to interest student For entrepreneurship . In a simultaneous test or together . Both variables are independent This influence interest student For entrepreneurship